Rejoinder to Dominiak on the necessity of easements - Block, Walter E. (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
Dominiak (2019) agrees with the Blockian proviso: homesteading in a bagel or donut format is illicit, since it allows the owner to control land (the hole, the territory in the middle) with which he has not mixed his labor. Thus, a person who does so must open up an easement allowing outside homesteaders through his property, and into this so-far virgin land. But, this author claims this proviso of Block’s does not go far enough. It should also be extended further, not only to incorporate the bagel format, but also in justification of easements through private property in emergencies, and soas to avoid entrapment. I strongly support Dominiak in his defense of the Blockian proviso againstcritics (Kinsella, 2007, 2009C) in the fi rst part of his excellent paper, but find I cannot agree with this second contention of his. In short, Dominiak agrees with Block regarding easements in the bagel case, but wants to extend this concept to when property owners are encircled, and thus trapped. In my view, extending easements to cases other than the bagel is incompatible with libertarianism’s emphasis on the sanctity of private property rights. Certain positive rights (to, in this case, movement) are essential to Dominiak’s argument. And these rights do not exist. Therefore, Dominiak’s argument is unsound.
Keywords: libertarianism; easements; homesteading; property rights; Blockian proviso; positive rights